Tantangan Dalam Penilaian Klinis Gejala Depresi pada Usia Lanjut - Fatma, Siti; Sunarti, Sri; Mardhiyah, Fairuz; Wirabhatari, Astika; Winstonly, Brian; Sunarti, Sr (RSUD Dr. Saiful Anwar Province of East Java, 2024)
Depression is one of the common mood disorder of the elderly, which can reduced the ability to rehabilitate and increased the likelihood of death from physical illnessess. Depressed older adults are less likely to endorse affective symptoms and more likely to display cognitive changes, somatic symptoms, and loss of interest than are younger adults. It is also frequently confused with the effects of multipel illnessess and the medicines use to treat them. Risk factors leading to late life depression are genetic vulnerabilities, cognitive diathesis, age associated neurobiological changes, insomnia, and stressful events. Combination therapy is cognitive behavioral therapy or acceptance and commitment therapy with antidepressant drugs.